2011
DOI: 10.1007/s00436-011-2465-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cryptosporidium parvum and Cryptosporidium hominis in human patients in Cairo, Egypt

Abstract: Cryptosporidium is a significant cause of diarrheal disease in developing and industrialized nations. Cryptosporidium hominis and Cryptosporidium parvum are the main agents of cryptosporidiosis in humans. In Egypt, very little is known about genetic structure of Cryptosporidium spp. Therefore, this study was designed to examine samples from sporadic cases of cryptosporidiosis in Egyptians in order to identify the species involved in infection as well as the transmission dynamics and distribution of the parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 29 publications
8
20
1
1
Order By: Relevance
“…Our study showed a predominance C. parvum over C. hominis. This result was in agreement with the results of another study in Egypt, where the predominant species were C. parvum over C. hominis [32], but contradictory to the results of another study in Egypt that showed an elevated prevalence of C. hominis over C. parvum [33]. Regarding the method of detection of Cryptosporidium infection, in the present work, both Ziehl-Neelsen stain and coproantigen detection methods were used.…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed a predominance C. parvum over C. hominis. This result was in agreement with the results of another study in Egypt, where the predominant species were C. parvum over C. hominis [32], but contradictory to the results of another study in Egypt that showed an elevated prevalence of C. hominis over C. parvum [33]. Regarding the method of detection of Cryptosporidium infection, in the present work, both Ziehl-Neelsen stain and coproantigen detection methods were used.…”
Section: Discussionsupporting
confidence: 87%
“…Most cases were recorded in Summer months (July, August and September 26 cases (52.0%)), which is in accordance with other studies in different regions in Egypt (El-Shazly et al 2007;Abd El Kader et al 2011). The summer seasonal diarrheal peak could be due to the coincidence with the recreational water season, reflecting the increased use of rivers, lakes, swimming pools and water parks (Yoder and Beach 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Human cryptosporidiosis caused by C. parvum mainly occurs in rural areas (12) and detection of the agent in persons with animal contact (10) refers to the zoonotic transmission (13,14). In the present study, C. parvum cases outnumbered C. hominis cases, suggesting a zoonotic transmission.…”
Section: Discussionmentioning
confidence: 44%